Pemberdayaan UMKM Lokal Kopi Berbasis Digital melalui Pemanfaatan Canva, CapCut, Digital Marketing, dan Digital Finance - Yulianingsih, Yulianingsih; Awa, Awa; Ismartaya, Ismartaya; Ari, Muhammad; Andiyansyah, Simaludin; Hanifah, Siti Zuhur; Ibrahim, Tubagus Maulana (Jurnal PKM Manajemen Bisnis, 2025)
The Community Service Program (PkM) in Karang Tengah Village, Babakan Madang District, Bogor Regency, addressed the challenges faced by local coffee-based MSMEs, particularly Kopi Gunung Wangun Dua, which lacked strong product identity, systematic financial management, and effective use of digital platforms. This program aimed to strengthen MSME capacity through integrated digital empowerment combining creative design, online marketing, and digital finance. The implementation followed five stages: observation, interviews, discussions, analysis, and direct training and mentoring. The results showed significant improvements: (1) stronger product branding through logos, trademarks, and professional packaging using Canva and CapCut, (2) wider market access via social media and marketplaces supported by digital marketing strategies, (3) improved financial literacy with training on bookkeeping, cost of production, and pricing, and (4) enhanced business legitimacy through the issuance of a Business Identification Number (NIB). These outcomes demonstrate that the PkM successfully fostered professional and sustainable business practices by integrating digital tools with participatory mentoring. The novelty of this program lies in the combined use of creative applications and digital finance training, which effectively increased the competitiveness and resilience of local MSMEs in a digital economy.